Mains Electricity Base Rate Minimization Under Specified Conditions of Power Consumption with the use of Capacitors - Alexander S. Demidov; Alexander S. Kochurov (RUDN Journal of Engineering Research)
The negative consequences of the peak selection of network products (electricity, water, gas, and other resources, including time distribution in computer programs) force the supplier to introduce tariff-based time payments. Thus, the question arises as to whether the consumer’s payment can indeed be minimized at a specific mode of product consumption if there is a system of its accumulation, that is, capacitor or storage, which replenishes or consumes its reserves at times of low and high tariff prices. To achieve this objective, it is necessary to make optimal use of accumulator resources, which can be drawn upon during periods of high tariffs and replenished when the need for them is less urgent and tariffs are lower. To achieve this, an appropriate mathematical problem is formulated (for the purposes of concretization, relating to the question of minimizing the payment for electricity consumption) that considers the operational characteristics of the storage and the different modes of energy consumption. This mathematical problem for the minimum can be solved using standard linear programming. The results of the numerical calculations of payments for a particular enterprise both without storage and with the use of capacitor are presented. The gain in payment was approximately 20 per cent.